Integrated Analysis of mRNA and Non-coding RNA Transcriptome in Pepper (Capsicum chinense) Hybrid at Seedling and Flowering Stages - Shu, Huang-ying; Zhou, He; Mu, Hai-ling; Wu, Shu-hua; Jiang, Yi-li; Yang, Zhuang; Hao, Yuan-yuan; Zhu, Jie; Bao, Wen-long; Cheng, Shan-han; Zhu, Guo-peng; Wang, Zhi-wei (Frontiers in Genetics, 2021)
Pepper is an important vegetable in the world. In this work, mRNA and ncRNA transcriptome profiles were applied to understand the heterosis effect on the alteration in the gene expression at the seedling and flowering stages between the hybrid and its parents in Capsicum chinense. Our phenotypic data indicated that the hybrid has dominance in leaf area, plant scope, plant height, and fruit-related traits. KEGG analysis showed that nine members of the plant hormone signal transduction pathway were up-regulated in the seedling and flowering stages of the hybrid, which was supported by weighted gene co-expression network analysis, that BC332_23046 (Auxin response factor 8), BC332_18317 (Auxin-responsive protein IAA20), BC332_13398 (Ethylene-responsive transcription factor), and BC332_27606 (Ethylene-responsive transcription factor WIN1) were candidate hub genes, suggesting the important potential role of the plant hormone signal transduction in pepper heterosis. Furthermore, some transcription factor families, including bHLH, MYB, and HSF were greatly over-dominant. We also identified 2,525 long ncRNAs (lncRNAs), 47 micro RNAs (miRNAs), and 71 circle RNAs (circRNAs) in the hybrid. Especially, down-regulation of miR156, miR169, and miR369 in the hybrid suggested their relationship with pepper growth vigor. Moreover, we constructed some lncRNA–miRNA–mRNA regulatory networks that showed a multi-dimension to understand the ncRNA relationship with heterosis. These results will provide guidance for a better understanding of the molecular mechanism involved in pepper heterosis.